Sustainable Energy without the hot air - MacKay, David J.C. (University of Cambridge, 2012)
Addressing the sustainable energy crisis in an objective manner, this enlightening book analyzes the relevant numbers and organizes a plan for change on both a personal level and an international scale—for Europe, the United States, and the world. In case study format, this informative reference answers questions surrounding nuclear energy, the potential of sustainable fossil fuels, and the possibilities of sharing renewable power with foreign countries. While underlining the difficulty of minimizing consumption, the tone remains positive as it debunks misinformation and clearly explains the calculations of expenditure per person to encourage people to make individual changes that will benefit the world at large.